Tolerance to high-intensity intermittent running exercise: do oxygen uptake kinetics really matter? - Buchheit, Martin; Hader, karim; Alberto, Mendez-Villanueva (Frontiers in Physiology, 2012)
We examined the respective associations between aerobic fitness (VO2max), metabolic control (VO2 kinetics) and locomotor function and various physiological responses to high-intensity intermittent running exercise (HIT) in team sport players. Eleven players (30.5 ± 3.6 y) performed a series of tests to determine their VO2max and the associated velocity (vVO2max), maximal sprinting speed (MSS) and VO2 kinetics at exercise onset in the moderate and severe intensity domains, and during recovery (VO2τoff SEV). Cardiorespiratory variables, oxygenation and electromyography (EMG) of lower limbs muscles and blood lactate concentration ([La]) were collected during a standardized HIT protocol consisting in 8 sets of 10, 4-s runs. During HIT, four players could not complete more than 2 sets; the others finished at least 5 sets. Metabolic responses to the 2 first sets of HIT were negatively correlated with VO2max, vVO2max, and VO2τoff SEV (r=-0.6 to -0.8), while there was no clear relationship with the other variables. VO2, oxygenation and [La] responses to the first 2 sets of HIT were the only variables that differed between the players which could complete at least 5 sets or those who could not complete more than 2 sets. Players that managed to run at least 5 sets presented, in comparison with the others, greater v O2max (ES=+1.5(0.4;2.7), MSS(ES=+1.0(0.1;1.9)) and training load (ES=+3.8 (2.8;4.9)). There was no clear between-group difference in any of the VO2 kinetics measures (e.g., ES=-0.1(-1.4;1.2) for VO2τon SEV). While VO2max and vVO2max are likely determinant for HIT tolerance, the importance of VO2 kinetics as assessed in the present study appears limited in the present population. Knowing the main factors influencing tolerance to high-intensity intermittent running exercise may assist practitioners in personalizing training interventions.